Sycamore promises [large type] - Colt, Paul (Wheeler Publishing large print western, 2018)
A young couple leaves Ohio for the promise of a new life on the Kansas plains. They settle a prime tract of farm land near Lawrence, Kansas. A second young couple slips the bonds of slavery in Missouri. Circumstance brings them together. Set against the backdrop of a nation divided over the issue of slavery, the young settlers fight to hold their land and realize the future that unites them. Opposed by powerful forces they face human treachery, hostile Indians, prejudice, and a bloody, burning prelude to war as they battle to hold a hard-won home and fulfill the promises of their future. Sycamore Promises is a sweeping personal saga told with attention to history so as to both entertain and inform.--Provided by Amazon.com.